PENGEMBANGAN MEDIA YOUTUBE SHORT VIDEO PENCEGAHAN DIABETES MELITUS - Abdullah, Muhammad Hizbi Abdullah; Lestari, Febri Sri (Jurnal Kesehatan Siliwangi, 2024)
Background: Indonesia ranks 5th globally in diabetes mellitus cases, with prevalence rising annually among individuals over 18. Health promotion media are essential for educating people, especially those aged 18-64, on diabetes prevention. YouTube Shorts is an effective medium due to its accessibility, enhancing attention to health information. Purpose: To produce YouTube Shorts as health promotion media regarding diabetes mellitus prevention for the audience and subscribers of the Smart Generations of Reality YouTube channel. Method: The research type utilizes Research and Development (R&D) with a 4D development model (define, design, development, disseminate). Result: The define stage revealed that the Smart Generations of Reality channel audience lacks awareness of diabetes prevention. The target audience prefers anime-style YouTube Shorts, which match their characteristics. The "entertain to educate" method is used for media delivery. The design stage includes pre-production, production, and post-production. The development stage involves expert validation and user testing, indicating high feasibility. The disseminate stage involves YouTube distribution. Conclusion: YouTube Shorts media for diabetes mellitus prevention is highly feasible to be used as an educational medium. Recommendations: Further research is needed to test the effectiveness or develop YouTube Shorts videos on diabetes mellitus prevention and use more current media relevant to the times for optimal results.